Extending the operational lifetimes of all-direct electron transfer enzymatic biofuel cells by magnetically assembling and exchanging the active biocatalyst layers on stationary electrodes - Herkendell, Katharina; Stemmer, Andreas; Tel-Vered, Ran (Nano Research, 2019)
Enzymatic biofuel cells promise green power generation from a variety of natural resources, yet these systems all suffer from time-dependent degradation effects, in particular progressing inactivation of enzymes, which severely limit the operational lifetimes of such power sources. To extend operational lifetimes, we introduce a method to magnetically exchange exhausted enzymes for fresh ones. To this end, anodic and cathodic enzymes or enzyme cascades are immobilized on carbon coated magnetic nanoparticles. Under the action of suitable magnetic field gradients, these nanoparticles are assembled on the respective stationary electrodes, or released from the electrodes for collection and subsequent exchange. We demonstrate this method on a fructose/oxygen consuming biofuel cell employing fructose dehydrogenase and bilirubin oxidase as well as on anodic and cathodic cascades employing fructose dehydrogenase/invertase and bilirubin oxidase/catalase, respectively. The enzyme-modified nanoparticles support direct electron transfer bioelectrocatalytic currents by wiring the redox active cofactors to the carbonaceous coating and from there to the electrode surfaces. The facile injection, assembly, and removal of enzyme-modified magnetic nanoparticles along with fuel solution provides a promising approach to extend the operational lifetime of enzymatic biofuel cells without the need for exchanging entire systems including chambers and electrodes. [Figure not available: see fulltext.].
Created from Fastlane, Scopus look-up
Keywords: direct electron transfer; enzymatic biofuel cell; enzyme cascade; lifetime; magnetic nanoparticle; recharge